2016
DOI: 10.1038/srep38532
|View full text |Cite
|
Sign up to set email alerts
|

Viral and bacterial co-infection in severe pneumonia triggers innate immune responses and specifically enhances IP-10: a translational study

Abstract: Mixed viral and bacterial infections are widely described in community-acquired pneumonia; however, the clinical implications of co-infection on the associated immunopathology remain poorly studied. In this study, microRNA, mRNA and cytokine/chemokine secretion profiling were investigated for human monocyte-derived macrophages infected in-vitro with Influenza virus A/H1N1 and/or Streptococcus pneumoniae. We observed that the in-vitro co-infection synergistically increased interferon-γ-induced protein-10 (CXCL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 44 publications
1
48
1
Order By: Relevance
“…Our data showed that individuals with higher levels of IP-10 prior to Spn inoculation had higher bacterial density. In a recent study, children with pneumonia with viral and bacterial (predominantly pneumococcal) co-infection had increased levels of IP-10 compared to children with just viral or bacterial pneumonia, which associated with disease severity 46 . Murine data suggests that IP-10 plays a direct role during pneumonia.…”
Section: Discussionmentioning
confidence: 96%
“…Our data showed that individuals with higher levels of IP-10 prior to Spn inoculation had higher bacterial density. In a recent study, children with pneumonia with viral and bacterial (predominantly pneumococcal) co-infection had increased levels of IP-10 compared to children with just viral or bacterial pneumonia, which associated with disease severity 46 . Murine data suggests that IP-10 plays a direct role during pneumonia.…”
Section: Discussionmentioning
confidence: 96%
“…In our series, IP-10 decreased over time in all groups. In a study with 74 children (≤5 years old) hospitalized with viral and/or bacterial community-acquired pneumonia, patients with identified mixed-detection had significantly higher serum IP-10 levels than those with a single detection [27]. An in vitro study has shown that compared to a single pathogen infection, a mixed bacterial-viral co-infection synergistically increased IP-10 expression by modulating the JAK-STAT signaling pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that mixed infections, defined as at least 2 types of pathogens contained in 1 sample, occur in more than half of cases of community-acquired pneumonia and are associated with more severe inflammatory disorders. 20,21 Interestingly, based on our data, TEM appeared to be far more sensitive in detecting mixed infections when compared with serological tests. In spite of these combined detection modalities, the overall rate of treatment failure was 20 of 106 (18.9%) in this study, which we thought was caused by severe systemic complications and antibiotic resistance.…”
Section: Discussionmentioning
confidence: 65%